Duty of Care of Universities toward Students’ Mental Health in India: A Doctrinal Analysis of Legal and Regulatory Frameworks (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Mental health concerns among university students have become an increasingly significant challenge for higher education institutions in India. Academic pressure, social transitions, financial difficulties, and competitive learning environments often contribute to psychological stress, making mental health support an important aspect of university governance. In recent years, policy debates and judicial developments have emphasized the responsibility of educational institutions to foster supportive environments that protect students’ psychological wellbeing. These developments raise important legal questions regarding the extent to which universities owe a duty of care toward students facing mental health challenges. This paper examines the duty of care of universities within the Indian legal and regulatory framework. Using a doctrinal research methodology, the study analyses relevant legal provisions, regulatory guidelines, and policy initiatives, including the Mental Healthcare Act, 2017 and the National Education Policy 2020, along with regulatory measures issued by the University Grants Commission. The paper argues that although mental health support is increasingly recognized in educational policy, the existing framework lacks clearly defined and enforceable obligations for universities, highlighting the need for stronger legal accountability and institutional mechanisms to protect student wellbeing.